Kvantitativne lastnosti slovenskega tvorjenega besedja v poskusnem besednodružinskem slovarju za črko B - Stramljič Breznik, Irena (Slavistična revija, 2005)
The article presents the quantitative features of the lexicon included in the dictionary compiled with the help of the computer program Slovar Red 2.0, 2003 by Tomaž Seliškar and the Section for terminological dictionaries at the Fran Ramovš Slovene language Institute at ZRC SAZU. The derivational features of the Slovene lexicon are established on the basis of only one twenty-fifth of (otherwise thoroughly analyzed) word families, therefore they can only be generalized with some reservation. For that it would be sensible to compile a complete word-family dictionay, as it would be possible on the given foundation ant with team work to improve certain segments of the treatment and in the end acquire a fairly realistic and empirically veriable picture of Slovene lexicon, which would be a good source for contrastive linguistic studies and various lexicographic projects.
Keywords: besedotvorje; leksika; leksikografija; lexicography; slovarji; Slovene; slovenščina; word formation